Hybrid nanocomposites based on electroactive hydrogels and cellulose nanocrystals for high-sensitivity electro–mechanical underwater actuation. (18th July 2017) - Santaniello, Tommaso; Migliorini, Lorenzo; Locatelli, Erica; Monaco, Ilaria; Yan, Yunsong; Lenardi, Cristina; Comes Franchini, Mauro; Milani, Paolo
Abstract: We report the synthesis, fabrication and characterization of a hybrid hydrogel/cellulose nanocomposite, which exhibits high-performance electro–mechanical underwater actuation and high sensitivity in response to electrical stimuli below the standard potential of water electrolysis. The macromolecular structure of the material is constituted by an electroactive hydrogel, obtained through a photo-polymerization reaction with the use of three vinylic co-monomers: Na-4-vinylbenzenesulfonate, 2-hydroxyethylmethacrylate, and acrylonitrile. Different amounts (from 0.1% to 1.4% w/w) of biodegradable cellulose nanocrystals (CNCs) with sulfonate surface groups, obtained through the acidic hydrolysis of sulphite pulp lapsheets, are physically incorporated into the gel matrix during the synthesis step. Freestanding thin films of the nanocomposites are molded, and their swelling, mechanical and responsive properties are fully characterized. We observed that the embedding of the CNCs enhanced both the material Young's modulus and its sensitivity to the applied electric field in the sub-volt regime (down to 5 mV cm −1 ). A demonstrator integrating multiple actuators that cooperatively bend together, mimicking the motion of an electro-valve, is also prototyped and tested. The presented nanocomposite is suitable for the development of soft smart components for bio-robotic applications and cells-based and bio-hybrid fluidic devices fabrication.